PELAKSANAAN PROGRAM PERBAIKAN GIZI MASYARAKAT OLEH DINAS KESEHATAN KOTA PEKANBARU - Nindy Sawitri; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
One of the government objectives is to realize the highest degree of health both individual and society health, as in the contents of Law No. 36 of 2009 Article 46 on health efforts. To objectify good health can be started from the improvement of nutritional status of the community, so it will reduce malnutrition cases in Indonesia.If we let it, it will be able to cause death in malnourished children under five. All areas in Indonesia today still have cases of malnutrition in children under five. Like in Riau province, Pekanbaru City which became the center of the provincial capital is also experiencing cases of malnutrition. Through Health Official of Pekanbaru City, Government of pekanbaru keep doing efforts to reduce the cases of malnutrition. The effort is stated by the Minister of Health Regulation number 23 of 2014 on efforts to improve nutrition. In article 20 stated about malnutrition management that aims to improve nutritional status with the priority of reducing the mortality rate for children under five malnutrition. The purpose of this research is to know how implementation and factors affect the implementation of the Community Nutrition Improvement Program in Pekanbaru City. The concept used is a management theory according to Sudirdjo in Manulang about management, which refers to four (4) elements in management, planning, organizing, directing, and supervising. The research uses a qualitative method with a descriptive data analysis. In the data collection, the researcher uses an interview technique, observation and documentation using a snowball sampling method as the source of information and data analysis with qualitative descriptive method. The results showed that in the implementation of the nutrition improvement program, there are some factors that become obstacles in implementing this program. The obstacles in running the community nutrition improvement program are not only related to the problems of the government related to the budget, but also the constraints of the community who have not fully participated to be active in every activity undertaken by the government related to nutritional health Keywords: Program, Implementation, Management